Health Care Professionals´ Freedom of Conscience and Legal Abortion in Argentina in a nutshell (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
In 2020, Argentina passed an act that legalized abortion for the first time in this country. Although in a restrictive way, the legislative body considered the dilemmas caused by legal abortion among health care professionals. Consequently, the new act contemplates conscientious objection for medical workers in a restrictive clause. This paper addresses the definition of this civil liberty and the reasons underlying its protection in medicine. To achieve that ending, the authors propose the following route: I) first, we focus on the concept of conscientious objection and its evolution and classification; II) then, legal protection of conscientious objection against abortion is examined; III) Also, the importance of its protection in medicine, from two perspectives: a) first, in relation with the aims of the medical science; b) secondly, from the perspective of doctor-patient relationship; IV) finally, we include some critical observations about the consequences of the current regulation.